Use of Adobe Flash as multimedia learning in Arabic language learning - Amrina Amrina; Mooh Amiin Najeed; Novia Indriyana (Yayasan Adra Karima Hubbi, 2022)
This study aims to find out whether there is a role of learning media using adobe flash in Arabic language learning in class VII Madrsah Ibtidaiyah. This research uses qualitative methods with a descriptive approach. The research was conducted for one week by conducting field observations on students of class VII Madrasah Tsanawiyah in Arabic subjects. Arabic lessons are one of the urgent subjects taught in educational institutions, both private and public. The material provided is adjusted to the cognitive level of students, in learning a foreign language, a learning method is needed. Learning methods that can be a stimulus for students to understand the lesson well. One of them is by utilizing advances in information technology that give birth to various products to support learning. For example, the adobe flash application is used as an Arabic learning medium for class VII Madrasah Tsanawiyah. This Arabic learning multimedia application has been successfully created and uses Arabic images, animations, sounds and rules according to the 2013 curriculum. The results showed that the adobe flash application is suitable for use as a learning medium for Arabic class VII Madrasah Ibtidaiyah Negeri.